Nanofluidic qPCR unable to detect and serotype Streptococcus pneumoniae in urine samples of hospitalized South African patients with community-acquired pneumonia - Olwagen, Courtney P.; Jeche, Tariro R.; Van Der Merwe, Lara; Nunes, Marta C.; Madhi, Shabir A.; Baillie, Vicky L. (Scientific reports, 2023)
Pneumonia is a major cause of death among adults living with HIV in South Africa, but the etiology of many cases remains unknown. This study evaluated the utility of a nanofluidic qPCR assay to detect and serotype Streptococcus pneumoniae in urine samples from patients hospitalized with community-acquired pneumonia (CAP). The nanofluidic qPCR assay was optimized to target 13 pneumococcal serotypes and 4 reference genes. Archived urine samples collected from patients > 15 years of age hospitalized with pneumonia between April 2018 and August 2019 were retrospectively tested using the nanofluidic qPCR assay, BinaxNOW urine antigen test, and standard LytA qPCR. Blood culture was undertaken on a subset of the samples at the discretion of the attending physician. Cohens' Kappa statistics were used to determine the concordance between the methods. Of the 828 adults hospitalized for CAP, urine samples were available in 53% (n = 439). Of those, a random subset of 96 (22%) samples underwent testing. Of the participants included in the final analysis, the mean age was 45.8 years (SD 16.2), 49% (n = 47) were female, 98% (n = 94) were black, and 66% (n = 63) were living with HIV infection. The nanofluidic qPCR method was able to detect PCV13 vaccine strains spiked into urine samples; however, the method failed to detect any pneumococcus in clinical samples. In comparison, 19% of the pneumonia cases were attributed to S. pneumoniae using urine antigen testing. Nanofluidic qPCR is unable to detect and serotype Streptococcus pneumoniae in urine samples of South Africans hospitalized with CAP.